[Rezension von: Dunn, Susan, A blueprint for war] - Berg, Manfred (Journal of American history, 2019)
According to the historian Susan Dunn, the twelve-year presidency of Franklin D. Roosevelt went through three transformative periods of roughly one hundred days
Gesehen am 12.06.2019
Keywords: Rezension